2014
DOI: 10.1159/000366395
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Placenta-Derived Mesenchymal Stem Cells Ameliorates Ischemia Induced Limb Injury by Immunomodulation

Abstract: Background: Peripheral artery disease (PAD) is a major health burden in the world. Stem cell-based therapy has emerged as an attractive treatment option in regenerative medicine. In this study, we sought to test the hypothesis that stem cell-based therapy can ameliorate ischemia induced limb injury. Methods: We isolated mesenchymal stem cells derived from human placentas (PMSCs) and intramuscularly transplanted them into injured hind limbs. Treatment with PMSCs reduced acute muscle fibers apoptosis induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…Similarly, intraperitoneal implantation of MSCs attenuated EAE via a systemic immunomodulatory effect without infiltrating the CNS [, ]. Intramuscular implantation of placental stromal cells was shown to improve recovery in an ischemia‐induced limb injury model via immunomodulation [] and to mitigate the lethal effects of radiation []. Our study showed that a mixture of maternal and fetal hPSCs were more effective than maternal cells alone [].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, intraperitoneal implantation of MSCs attenuated EAE via a systemic immunomodulatory effect without infiltrating the CNS [, ]. Intramuscular implantation of placental stromal cells was shown to improve recovery in an ischemia‐induced limb injury model via immunomodulation [] and to mitigate the lethal effects of radiation []. Our study showed that a mixture of maternal and fetal hPSCs were more effective than maternal cells alone [].…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have also suggested that stromal cells isolated and expanded from different a Department of Neurology, The Agnes Ginges Center for Human Neurogenetics, and b Laboratory of Radiobiology and Biotechnology, Sharett Institute of Oncology, Hadassah Hebrew University Medical Center, Jerusalem, Israel layers of the human placenta (human placental stromal cells [hPSCs]) might represent a valid option for cell therapy with significant immunomodulatory properties [12][13][14][15]. This cellular platform is both ethically accepted and easily expandable to produce large batches of an off-the-shelf cell product for allogeneic implantation.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, MSCs are also called resident stem cells and constitute a reserve to replace damaged cells because they are capable of differentiating into a wide variety of cellular types, which is why they have been advocated in tissue-regenerative therapies [146]. MSCs have also been utilized for limb ischemia in both animals and humans with a low level of benefit so far [147][148][149][150]. To improve their potential, some researchers have defended their combination with GH.…”
Section: Gh and Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…On the other hand, immunomodulation effects of MSC treatment for limb ischemia have also previously been demonstrated. Studies have analyzed that P-MSCs inhibit the secretion of pro-inflammatory cytokines, such as IL-6 and TNF-α, whereas they induce the secretion of anti-inflammatory mediators, such as IL-10 [24][25][26]. Moreover, a prolonged inflammatory phase mediated by excessive proinflammatory cytokines is one of the biological characteristics of non-healing foot ulcers [27].…”
Section: Discussionmentioning
confidence: 99%